Identification of Neotropical blow flies of the genus Calliphora Robineau-Desvoidy (Diptera: Calliphoridae) with the description of a new species - Whitworth, Terry; Rognes, Knut (Zootaxa, 2012)
A key to the six known species of Calliphora Robineau-Desvoidy (Diptera: Calliphoridae) from the Neotropical Regionis given. Species distributions and key characters are discussed. Calliphora irazuana Townsend, 1908 is resurrected as avalid name for a species found in Central America and Mexico, stat. nov. Calliphora triseta sp. nov. is described fromnumerous specimens from Costa Rica, El Salvador and Mexico. Nominal species Calliphora nigra Mello, 1974 and Cal-liphora antojuanae Mariluis, 1982 are synonymized with Calliphora nigribasis Macquart, 1851, n. syn. An Appendix isprovided that clarifies the status of the names Calliphora peruviana Robineau-Desvoidy, 1830, Lucilia peruviana Robineau-Desvoidy, 1830, and Calliphora peruviana Macquart, 1851.